An open-circuit fault diagnosis approach for single-phase three-level neutral-point-clamped converters - Ge, Xinglai (2020)
This paper presents a model-based open-circuit fault diagnosis approach for single-phase three-level neutral-point-clamped (3LNPC) converters in electric railway application. The diagnosis algorithm, which only requires the signals existing in the control system, not only detects open-circuit faults but also identifies the faulty device among the transistors and clamping diodes. The mixed logical dynamic (MLD) model of the converter is built to estimate the grid current. The residual generated from the measured current subtracting the estimated one is analyzed under different open-circuit faults. According to the characteristics of the residual changing rate, the proposed approach allows fault localization. The proposed method is effective both in traction and regenerative braking operation and has fast diagnosis speed. Hardware-in-the-loop (HIL) experiments are carried out to verify the effectiveness of the proposed fault diagnosis algorithm.